Pemodelan Pengaturan Kecepatan Motor Induksi dengan Pulse Widht Modulation dengan Matlab - zainal abidin (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2019)
Alternative methods and modeling control of motor speed with the voltage regulation method currently used, namely the constant Volt / Hertz method with Pulse With Modulation (PWM) with several advantages and disadvantages and showing possible advantages and disadvantages to achieve the new method compared to the used today.The characteristics of the use of PWM can be studied together with the use of Matlab / Simulink modeling.